Metode dan Strategi Pembelajaran Medication Administration pada Pendidikan Keperawatan untuk Mencegah Medication Error - Dianti, Puteri; Musharyanti, Lisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify various learning methods that have been used in teaching medication safety. The research method is a scoping review where articles are taken from several databases such as PubMed, ProQuest, Science Direct, and Springer Link from year to year. Keywords used include